Improvement of the first flux entry field by laser post-treatment of the thin Nb film on Cu. (30th April 2021) - Ries, R; Seiler, E; Gömöry, F; Medvids, A; Onufrijevs, P; Pira, C; Chyhyrynets, E; Malyshev, O B; Valizadeh, R
Abstract: In superconducting radiofrequency accelerating cavities for particle accelerators, the Nb/Cu structure is one of the alternatives to bulk Nb but R&D is required to achieve a reproducible performance that competes with bulk Nb. The DC entry field H en and critical temperature were studied in the thin Nb films deposited by magnetron sputtering on Cu substrate. The Nb surfaces were further treated by Nd:YAG laser at four energy doses ( D 1 = 350, D 2 = 233, D 3 = 175 and D 4 = 140 J cm −2 ). The superconducting properties and other characteristics obtained by atomic force microscope, scanning electron microscope and x-ray diffraction were compared before and after laser treatment. The laser treatment increased the field of first flux entry by up to 65% compared to a non-irradiated sample. The laser irradiation also led to reduction of surface roughness, improvement of the surface morphology, reduction in crystallite size and increase of lattice parameter.